Pos Malaysia Berhad a case study: absenteeism among postman in Negeri Sembilan / Nur Syahirah Mansor - Mansor, Nur Syahirah (Faculty of Business and Management, 2010)
This purpose of this study is to investigate the effect of absenteeism among the postman at Pos Malaysia Berhad in Negeri Sembilan. Researcher was interviewed four respondent who are directly involved in resolving the problem of absenteeism in Pos Malaysia Berhad especially in Negeri Sembilan. From the study, researcher found that absenteeism may lead to a few problems such as carryover of mails and dissatisfaction of customers. After some discussion and meeting with the interviewee, researcher may conclude that factor that persuade to absenteeism is personal factor by the postman himself. There are various solution might be used by Pos Malaysia Berhad to solve the problem of absenteeism like improve the environment of workplace and effective communication between top management and postman.